2022
DOI: 10.3389/fcvm.2021.809580
|View full text |Cite|
|
Sign up to set email alerts
|

The Regulation Mechanisms and Clinical Application of MicroRNAs in Myocardial Infarction: A Review of the Recent 5 Years

Abstract: Myocardial infarction (MI) is the most frequent end-point of cardiovascular pathology, leading to higher mortality worldwide. Due to the particularity of the heart tissue, patients who experience ischemic infarction of the heart, still suffered irreversible damage to the heart even if the vascular reflow by treatment, and severe ones can lead to heart failure or even death. In recent years, several studies have shown that microRNAs (miRNAs), playing a regulatory role in damaged hearts, bring light for patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 151 publications
(136 reference statements)
1
11
0
Order By: Relevance
“…miR-548 downregulated HMGB1 in human amniotic epithelial cells ( 68 ) and activation of HMGB1 in bone marrow stem cells stimulates proliferation and angiogenesis ( 69 ). Therefore, delivery of miR-548 to recipient HCAEC may engage the HMGB1 pathways and therefore reduce proliferation and tube formation, Our results also indicate that all of the miRNAs that were reported to induce angiogenesis in coronary endothelium post-ischemia ( 14 ) are, in fact, not detectable in our EV populations and perhaps it is not surprising that the functional miRNA cargo in our vesicles do not support pro-angiogenic mechanisms ( Figure 7 ). Future studies are granted to validate the role of miRNA EVs in coronary angiogenesis and to identify potential therapeutic targets.…”
Section: Discussionmentioning
confidence: 72%
“…miR-548 downregulated HMGB1 in human amniotic epithelial cells ( 68 ) and activation of HMGB1 in bone marrow stem cells stimulates proliferation and angiogenesis ( 69 ). Therefore, delivery of miR-548 to recipient HCAEC may engage the HMGB1 pathways and therefore reduce proliferation and tube formation, Our results also indicate that all of the miRNAs that were reported to induce angiogenesis in coronary endothelium post-ischemia ( 14 ) are, in fact, not detectable in our EV populations and perhaps it is not surprising that the functional miRNA cargo in our vesicles do not support pro-angiogenic mechanisms ( Figure 7 ). Future studies are granted to validate the role of miRNA EVs in coronary angiogenesis and to identify potential therapeutic targets.…”
Section: Discussionmentioning
confidence: 72%
“…Jaguszewski et al ( 22 ) reported a signature of four circulating miRs as a robust biomarker to distinguish tako-tsubo syndrome from patients with AMI, which highlighted distinct characteristics of the miR profile in clinically indistinguishable cardiovascular diseases. Various miRs have been widely studied for their modulation of cardiomyocyte apoptosis, inflammation, angiogenesis, and fibrosis of AMI ( 23 ). Of these, miR-214 is highly expressed in the sera of elderly patients with AMI and may inhibit myocardial cell apoptosis by inhibiting the expression of miR-214 target genes, including the p53-upregulated modulator of apoptosis, PTEN, Bcl-2-associated X, and caspase 7 ( 24 ).…”
Section: Discussionmentioning
confidence: 99%
“…ncRNAs play a significant role in the development of cardiovascular disease by exerting essential functions in the regulation of gene expression at both the transcriptional and posttranscriptional levels. miRNAs offer a flexible means of gene control and have a role in several cardiovascular processes 86 . For example, miRNAs play a crucial role in modulating gene expression through posttranscriptional mechanisms.…”
Section: Noncoding Rnas In Cardiomyopathiesmentioning
confidence: 99%